MOTIVASI KELUARGA DALAM MENITIPKAN LANSIA PADA PANTI SOSIAL TRESNA WERDHA KHUSNUL KHOTIMAH PEKANBARU - Raja Tommy Chandra I; Syamsul Bahri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research done in Tresna Werdha Khusnul Khotimah Social Homes Pekanbaru with the aim of knowing family motivation selecting elderly to social homes. This research was conducted with quantitative methods and data collection is done by questionnaire, interview and documentation. The sampling technique used is saturated sampling or census method with 75 samples.The results of this research showed that family motivation selecting elderly in Tresna Werdha Khusnul Khotimah Social Homes Pekanbaru mostly impact by physical and biological needs that is food, drink, and residence needs for elderly and then social needs for friendship, social interaction, loved and loving each others and accepted in social environments. Conection between elderly and family has a good and bad conection that impact sometimes writer found there is no one visit or comunicate for bad conection with family. Keywords : Family Motivation, Elderly, Social Homes